Implementasi Kebijakan Peningkatan Partisipasi Pemilih Pemula melalui Program “Goes To School di Kota Surabaya - Haniardi, Deva Putri; Hariyoko, Yusuf; Basyar, M Roisul (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This research aimed to describe the implementation of policies to increase the participation of first-time voters through the KPU’s “Goes To School program in Surabaya. This study uses a qualitative approach with a research method based on Smith (1973) implementation theory, which consist of four stages of implementation as indicators: idealized policy, target groups, implementing organization, and environmental factor. The data collection techniques used are interviews, observations, and documents. The number of informants is six participants, including KPU Staff, BAWASLU Staff, LSM Staff, Media, Khadijah High School Students, and first-time voter participant. The result show that each indicator used in the implementation of the election participation policy through the “Goes To School program in Surabaya has shown improvement and has been quite succesful as an effort to reduce the number of non-voters. ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan implementasi kebijakan peningkatan partisipasi pemilih pemula melalui program